Dynamic control of low-Z material deposition and tungsten erosion by strike point sweeping on DIII-D. (August 2017) - Guterl, J.; Abrams, T.; Ding, R.; Guo, H.Y.; Rudakov, D.; Wampler, W.
Highlights: Carbon deposition on W between ELMs investigated in DIII-D in H-mode plasma. No C deposition on W observed during these experiments, even at high densities. Regime of C deposition on W between ELMs however predicted by the ERO model. ELMs may induce significant carbon erosion from tungsten surface. Abstract: Carbon deposition on tungsten between ELMs was investigated in DIII-D in semi-attached/detached H-mode plasma conditions using fixed outer strike point (OSP) positions. Carbon deposition during plasma exposure of tungsten was monitored in-situ by measuring the reflectivity of the tungsten sample surface. No significant carbon deposition, i.e., without strong variations of the reflectivity, was observed during these experiments including discharges at high densities. In contrast, ERO modeling predicts a significant carbon deposition on the tungsten surface for those high density plasma conditions. The surface reflectivity decreases with methane injection, consistent with increased carbon coverage, as expected. The sweeping of OSP leads to a pronounced increase of the surface reflectivity, suggesting that the strike point sweeping may provide an effective means to remove carbon coating from tungsten surface. The ERO modeling however predicts again a regime of carbon deposition for these experiments. The discrepancies between carbon deposition regime predicted by the ERO model and the experimental observations suggest that carbon erosion during ELMs may significantly affect carbon deposition on tungsten.